Financial sector in India - "Chakrabarti, Rajesh" (New Delhi, 2006)
Considered the most sophisticated and complex part of the economy, the financial system keeps the entire economy functioning smoothly. This volume captures and analyses developments and trends in different components of this system of the Indian economic landscape, such as the equity markets, foreign exchange and commodity markets, banking and micro-finance sectors, and in corporate governance.
Keywords: Financial sector - India